Combined Effects of Ethnicity and Education on Burden of Depressive Symptoms over 24 Years in Middle-Aged and Older Adults in the United States - Assari, Shervin (Brain Sci, 2020)
Ethnicity and educational attainment are among the major social determinants of depression in the general population. While high education credentials protect individuals against depressive symptoms, this protection may be weaker for ethnic minority groups such as Hispanic Whites compared to the majority group (non-Hispanic Whites). Built on marginalization-related diminished returns (MDRs), the current study used 24-year follow-up data from a nationally representative sample of middle-aged and older adults to explore ethnic variation in the protective effect of education levels against the burden of depressive symptoms over time. Data for this analysis were borrowed from the Health and Retirement Study (HRS 1992–ongoing), a nationally representative longitudinal study. HRS followed 8314 middle-aged and older adults (50+ years old) for up to 24 years. From this number, 763 (9.2%) were Hispanic White, and 7551 (90.8%) were non-Hispanic White Americans. Education level was the independent variable. We had two outcomes. Firstly, using cluster analysis, individuals were categorized to low- and high-risk groups (regarding the burden of depressive symptoms over 24 years); secondly, average depressive symptoms were observed over the 24 years of follow up. Age and gender were the covariates. Ethnicity was the moderator. Linear and logistic regression were used for analysis. Logistic regression showed that, overall, high educational credentials reduced the odds of chronic depressive symptoms over the 24 years of follow-up. Linear regression also showed that higher years of education were associated with lower average depressive symptoms over time. Both models showed statistically significant interactions between ethnicity and graduation, indicating a smaller protective effect of high education against depressive symptoms over the 24 years of follow-up time among Hispanic with respect to non-Hispanic White people. In line with the MDRs, highly educated Hispanic White Americans remain at high risk for depressive symptoms, a risk that is unexpected given their education. The burden of depressive symptoms, however, is lowest for highly educated non-Hispanic White Americans. Policies that exclusively focus on equalizing educational gaps across ethnic groups may fail to eliminate the ethnic gap in the burden of chronic depressive symptoms, given the diminished marginal health return of education for ethnic minorities. Public policies must equalize not only education but also educational quality across ethnic groups. This aim would require addressing structural and environmental barriers that are disproportionately more common in the lives of ethnic minorities across education levels. Future research should test how contextual factors, residential segregation, school segregation, labor market practices, childhood poverty, and education quality in urban schools reduce the health return of educational attainment for highly educated ethnic minorities such as Hispanics.